Pattern of neonatal morbidity and mortality: A retrospective study in a special newborn care unit, Mumbai - Randad, Kailas; Choudhary, Dilipkumar; Garg, Ankur; Jethaliya, Rahul (Indian Journal of Child Health, 2020)
Background: Despite advances in perinatal and neonatal care, neonatal mortality is still high in developing countries, like India. Special neonatal care units (SNCUs) have been set up at different levels of health-care delivery system to provide quality newborn care services to meet this challenge. Aim: This study was undertaken to study morbidity and mortality pattern of neonates admitted at SNCU. Materials and Methods: This retrospective study was conducted in a newly started SNCU in the Western suburbs of Mumbai, India. The study included all babies admitted between 0 and 28 days of life over a period of 1 year. The babies were categorized based on gestational age and birth weight. Results: A total of 531 babies were admitted during the study period, including 125 outborn babies. About 25% of babies were preterm (<37 weeks), and 40% of babies were low birth weight (LBW) including 4.14% very LBW and 2.44% extremely LBW babies. Neonatal jaundice, respiratory distress, prematurity, LBW, suspected sepsis, and perinatal depression were common indications for admission. Only 11 (2.07%) babies required antibiotics. The overall mortality rate was 1.55%, with birth asphyxia being the leading cause of death. Conclusion: Results of this study showed that simple measures for the prevention of morbidity and mortality related to prematurity and sepsis may avoid excessive use of antibiotics and reduce overall morbidity and mortality of neonates admitted in SNCU/neonatal intensive care units.